RESEARCH ON CO-SIMULATION OF FINITE ELEMENT METHOD AND THE MULTI BODY DYNAMICS OF THE CRANKSHAFT FATIGUE LIFE - CUI GuangJun (Jixie qiangdu)
In this paper,on the basis of the finite element method,the dynamic simulation analysis and fatigue analysis,co-simulation of finite element and multibody dynamics was used to predict the crankshaft fatigue life. MSC. Nastran was used to make the modal analysis for getting the modal neutral file（ *. mnf）. The rigid crankshaft was replaced by the flexible crankshaft,then this paper built a coupled multi-body dynamics model of engine by using ADAMS. Load history for the crankshaft is calculated in ADAMS,then import the gotten. dac files into MSC. Fatigue. Analysis of the crankshaft fatigue life is completed.The results may be valuable for optimal design of crankshaft.